2020
DOI: 10.1016/j.cviu.2020.103010
|View full text |Cite
|
Sign up to set email alerts
|

High-speed multi-person pose estimation with deep feature transfer

Abstract: Recent advancements in deep learning have significantly improved the accuracy of multi-person pose estimation from RGB images. However, these deep learning methods typically rely on a large number of deep refinement modules to refine the features of body joints and limbs, which hugely reduce the run-time speed and therefore limit the application domain. In this paper, we propose a feature transfer framework to capture the concurrent correlations between body joint and limb features. The concurrent correlations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
(85 reference statements)
0
5
0
Order By: Relevance
“…By incorporating part-based assessment, the potential to provide further analytic cues for CP prediction and the identification of CP sub-types is enhanced [43]. As such, alternative methods have been proposed to better model human shape and motion, such as pose estimation [9], [22].…”
Section: B Automated Optical Flow-based Methodsmentioning
confidence: 99%
“…By incorporating part-based assessment, the potential to provide further analytic cues for CP prediction and the identification of CP sub-types is enhanced [43]. As such, alternative methods have been proposed to better model human shape and motion, such as pose estimation [9], [22].…”
Section: B Automated Optical Flow-based Methodsmentioning
confidence: 99%
“…Some works also use neural networks to learn the parameters of a 3DMM model for face recovery, which combines the advantage of neural networks in parameter fitting and the 3DMM model in recovering stable geometric and textural representations [ 6 , 7 ]. The advancement of deep learning solutions, however, comes with the requirement of more training data [ 35 , 36 , 37 , 38 , 39 ]. Due to the high cost of acquiring 3D face scanning data, some methods that rely on weekly-supervised learning have also been proposed to reconstruct faces through synthesis by analysis [ 6 , 9 , 17 , 34 ].…”
Section: Related Workmentioning
confidence: 99%
“…The consistency of several elements throughout time can be used to assess a joint's reliability, and learning the weights of dependability terms improves the performance of the classifier [14]. To capture the concurrent correlations between body joint and limb data, Huang et al suggested a feature transfer paradigm [15]. Concurrent correlations of these features can help build a structural link that might improve the network's inferences while reducing the requirement for refinement modules.…”
Section: Related Workmentioning
confidence: 99%